Desempeño laboral de los empleados de la Empresa Suanfarma de la ciudad de Babahoyo periodo 2021. - Ortega Tomala, Lina Evelin (2022)
The purpose of this research work is to carry out a treatment of work performance in a pharmaceutical company. This conceptually is described as those actions and behaviors executed by workers that help to achieve the objectives proposed for the success of companies. At present, administrative management has branded job performance as one of the most significant aspects when it comes to growing in the business world, so this case study investigates how having a good job performance is related to proper management. of the san farma company, which is located in the province of Los Ríos in the city of Babahoyo and is dedicated to the sale of medical and pharmaceutical products. To demonstrate this relationship, it was necessary to know the importance of job performance with theoretical bases duly supported, in addition, a descriptive methodology was used that led to the study of the population that is made up of the people who work in this pharmaceutical company, who are I apply the survey technique based on a questionnaire of questions that allowed to know the relationship that exists between these variables investigated.